Influence of 5-hydroxymethyluracil on the dynamics of angiogenic growth factors in the perioperative period of surgical myocardial revascularization: results of a randomized trial - B. A. Oleynik; V. V. Plechev; V. A. Evdakov; R. I. Izhbuldin; N. Sh. Zagidullin (Российский кардиологический журнал, 2023)
Aim. To evaluate the effect of 5-hydroxymethyluracil on the dynamics of angiogenic growth factors in the perioperative period of surgical myocardial revascularization.Material and methods. This prospective, randomized, single-center study included two following groups: experimental group — 25 patients in the perioperative period of coronary artery bypass grafting (5 days before and 14 days after surgery) receiving 5-hydroxymethyluracil (at a dose of 500 mg 3 times a day) in addition to standard therapy; control group — 25 patients receiving standard therapy. The groups were comparable in terms of sex, age, main clinical and functional characteristics and features of surgical intervention. In patients, quantitative indicators of angiogenic growth factors in peripheral blood taken 5 days before and 14 days after surgery were studied by enzyme immunoassay: human vascular endothelial growth factor A (VEGF-A), human hepatocyte growth factor (hHGF), insulin-like factor growth 1 (IGF-1) and basic fibroblast growth factor (bFGF).Results. In the experimental group of patients, while taking 5-hydroxymethyluracil, there was a significant increase in the peripheral blood concentration of following growth factors compared with the control group: VEGF-A by 26,90% (p=0,0246), IGF-1 by 44,89% (p=0,0011), bFGF by 60,0% (p=0,0006). The hHGF concentration also turned out to be higher by 19,90%, but did not reach the level of statistical significance (p=0,2836).Conclusion. The use of 5-hydroxymethyluracil, a representative of pyrimidines, in the perioperative period of surgical myocardial revascularization leads to a significant increase in peripheral blood of such angiogenic growth factors as VEGF-A, IGF-1, and bFGF.